Perspectives on translation of positronium imaging into clinics - Pawel Moskal; Pawel Moskal; Pawel Moskal; Ewa Ł. Stępień; Ewa Ł. Stępień; Ewa Ł. Stępień (Frontiers in Physics, 2022)
The image of positronium properties created in the patient’s body during PET examination tells about the inter- and intra-molecular structure of the tissue and the concentration of bio-active molecules in the tissue [2–4]. In this article, we advocate the opinion that total-body PET systems, thanks to their high imaging sensitivity and high time resolution, open up the prospect of translating positronium imaging into clinics.